2018
DOI: 10.1093/tbm/iby027
|View full text |Cite
|
Sign up to set email alerts
|

A multicomponent behavioral intervention for smoking cessation during pregnancy: a nonconcurrent multiple-baseline design

Abstract: Given serious consequences of maternal smoking, we aimed to develop and test a multicomponent behavioral intervention to enhance smoking cessation during pregnancy. In this nonconcurrent, multiple-baseline intervention pilot study, 48 daily smoking pregnant women (mean 13.7 weeks of gestation) were recruited from Buffalo, NY, USA. Upon completion of the repeated baseline smoking monitoring (up to 3 weeks), 30 continuous smokers received a contingent financial incentive-based intervention with three additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Maternal smoking during pregnancy also consistently mediated the effects of both SES measures on childhood obesity. Our result was supported by two previous studies (37,38) smoking abstinence rate through a multicomponent intervention (41). In addition, we found that intervention-assisted maternal smoking cessation, especially if quitting occurred before 27 weeks, could substantially reduce the risk of rapid infant BMI gain (42).…”
Section: Maternal Smoking During Pregnancysupporting
confidence: 89%
See 1 more Smart Citation
“…Maternal smoking during pregnancy also consistently mediated the effects of both SES measures on childhood obesity. Our result was supported by two previous studies (37,38) smoking abstinence rate through a multicomponent intervention (41). In addition, we found that intervention-assisted maternal smoking cessation, especially if quitting occurred before 27 weeks, could substantially reduce the risk of rapid infant BMI gain (42).…”
Section: Maternal Smoking During Pregnancysupporting
confidence: 89%
“…It is effective and safe to use behavioral, pharmaceutical, and economic interventions to assist pregnant women to stop smoking (40). For example, our own smoking cessation intervention achieved a 63.3% smoking abstinence rate through a multicomponent intervention (41). In addition, we found that intervention‐assisted maternal smoking cessation, especially if quitting occurred before 27 weeks, could substantially reduce the risk of rapid infant BMI gain (42).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, smoking cessation programs included messages describing how tobacco companies have knowingly worked to persuade smokers to use products without any regard to their health, a strategy termed tobacco industry denomalization [50]. In addition, smoking cessation programs targeting secondhand smoke have worked to hold smokers accountable for their actions around their family members or during pregnancy [51, 52]. However, this is its first report as an outcome of an intervention, holding individual smokers accountable for their behavior.…”
Section: Discussionmentioning
confidence: 99%
“…There may be a hard core of individual mothers/parents who are unable to stop smoking, even knowing the risks to their baby. Some evidence exists that specific behavioural techniques may have an impact on prenatal smoking cessation [47][48][49], but the complexities around cessation in relation to pregnancy and childbirth need further interventional analysis. Despite these limitations, there may still be the benefit of incorporating smoking cessation information into parent awareness packages [8], while awaiting more effective interventions and primary preventive packages.…”
Section: Smoking Cessation and Infant Mortalitymentioning
confidence: 99%